(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article discusses the essence of budgeting. It is emphasized that in budgeting there is a transition from traditional budgeting to new, alternative lines of budgeting. Through the study of various sources, it has been investigated that traditional budgeting in the use process has had many shortcomings, which sometimes led to the rejection of its use (unrealistic strategic indicators, the variability of the macroeconomic environment, deterioration of corporate culture during the competition for the budget). Analyzed alternative approaches to traditional budgeting. In particular: Rolling forecast, Last year plus percentage, Bottom up, Top down, Activity based budgeting, Zero based budgeting, Demand pull, Driver-based planning. Also, attention is paid to such methods of budgeting, as budgeting on the basis of priorities, conference decisions, budgeting on the basis of performance, participation in the budget, budgeting with limited resources. It is concluded that all these new directions of budgeting combine the basing on a marketing approach in which strategic decisions of organizations and enterprises are based on the study of the needs of consumers of goods and services. Also, there are mechanisms where end consumers are the ones who make final decisions about directing funds and resources. This made it possible to assume the application of another approach to marketing budgeting as a management technology, designed to develop and implement the strategic objectives of an enterprise or organization aimed at shaping and meeting the needs of consumers.